Draft Laws on Administrative Court in the Interwar Period in Lithuania - Deviatnikovaitė, Ieva (Teisė, 2018)
[only abstract and summary in English; full article and abstract in Lithuanian]The very first law under which Lithuanian administrative courts were established was adopted in 1999. However, the predecessors of the Administrative Court (the Commission of Legal Ministerial Advisors, Complaints and Remanding Commission of the Seimas, State Council) were created in the third decade of the 20th century. Notwithstanding this, these authorities could not match the judicial review of public administrators’ activity. Consequently, the first draft laws on the Administrative Court were drafted in the fourth decade. There were over ten of such drafts but only two remained. The goal of the article is to reveal the content and the background of draft laws on the Administrative Court developed in 1932 and 1940, which were found in the Wroblewski Library Manuscript Division.SummaryThe predecessors of the administrative court were created in the third decade of the 20th century in Lithuania. Notwithstanding, these authorities could not match the judicial review of public administrators’ activity. It is noteworthy that sometimes the Senior Tribunal performed the functions of the administrative court and reviewed the legality of administrative acts. However, some laws did not provide the possibility to challenge administrative acts in the courts. That was the main reason to create Law on the Administrative Court of the Republic of Lithuania.There were a number of attempts to establish judicial review in Lithuania in various laws: in Constitutions, State Council Statute, Law on the Judicial System. Around 10 draft laws on the Administrative Court were prepared by the State Council and the Seimas Commission. However, these attempts were unsuccessful.The first draft law on the Administrative Court was drafted in 1932 by the State Council. The main proposals of this document were: first, the Administrative Court is an Administrative Division of the Supreme Court of Lithuania; second, the Administrative Court disposes general jurisdiction of judicial review of individual or regulatory administrative acts due to the violation of subjective rights of natural or legal person; third, the Administrative Court is the only judicial instance and before bringing an action into court, a plaintiff must go through all lower review processes. The draft law created in 1940 by the Seimas Commission was almost the same but more detailed in the provisions of administrative process, what is more, the Administrative Court was proposed to be a separate judicial body.The main initiators of the Law on the Administrative Court were two lawyers: member of the State Council, judge of the Senior Tribunal, ad hoc judge of the Permanent Court of International Justice, constitutional and administrative law scholar M. Romeris and Memel Territory Governor, Meyer of Kaunas, member of the Seimas and last Prime Minister A. Merkys.
Keywords: none